PROPOSTA DE DIRETRIZES PARA PROJETO DE TERCEIRIZAÇÃO NO SERVIÇO PÚBLICO. ESTUDO DE CASO NO INMETRO. - Barreto, Cláudio William da Conceição (2010)
The general objective of this study is the formulation of draft guidelines for structuring Outsourcing Project in the Public Service. The research method used was supported in bibliographic search and document research in Brazilian public institution. The results aim the formulation of guidelines on which the public manager needs to be guided to provide regularity legal, administrative and financial to outsourcing in government agencies.